Effectiveness and sustainability of a motor-cognitive stepping exergame training on stepping performance in older adults: a randomized controlled trial - Hauer, Klaus; Werner, Christian (European review of aging and physical activity, 2020)
Training effects reported for stepping exergames on stepping performances in older adults often based on not comprehensively validated outcomes measures, and follow-up data on their sustainability are lacking. The aim of this study is to evaluate the effectiveness and sustainability of a motor-cognitive stepping exergame training on the stepping performance in older adults.